2005
DOI: 10.1158/1078-0432.ccr-04-1713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imatinib on Monocyte-Derived Dendritic Cells Are Mediated by Inhibition of Nuclear Factor-κB and Akt Signaling Pathways

Abstract: Dendritic cells are the most powerful antigen-presenting cells playing a decisive role for the initiation and maintenance of primary immune responses. However, signaling pathways involved in the differentiation of these cells have not been fully determined. Imatinib is a novel tyrosine kinase inhibitor effective against Abl kinases, c-Kit, and plateletderived growth factor receptor. Using this compound, we show that human monocyte-derived dendritic cells generated in the presence of therapeutic concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 77 publications
7
60
1
3
Order By: Relevance
“…Of note, phosphorylation of I B␣ and subsequent NF-B DNA binding was also inhibited by imatinib preexposure, showing that imatinib impaired LPS-induced activation of NF-B. Imatinib reduced only nuclear translocation of the p65, while the p50 subunit remained unaffected, which is in line with previous data showing that imatinib modulates distinct NF-B subunits depending on the cell type studied (3,23). It is noteworthy that imatinib targets only tyrosine kinases, which excludes it as an direct inhibitor of the serine͞threonine kinase family member I B kinase (24).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of note, phosphorylation of I B␣ and subsequent NF-B DNA binding was also inhibited by imatinib preexposure, showing that imatinib impaired LPS-induced activation of NF-B. Imatinib reduced only nuclear translocation of the p65, while the p50 subunit remained unaffected, which is in line with previous data showing that imatinib modulates distinct NF-B subunits depending on the cell type studied (3,23). It is noteworthy that imatinib targets only tyrosine kinases, which excludes it as an direct inhibitor of the serine͞threonine kinase family member I B kinase (24).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, inhibition of p38 MAPK and͞or MEK1 might contribute to the observed effects on myeloid cells via inhibition of NF-B. Activation of the latter has recently been shown to be inhibited by imatinib in CD34 ϩ progenitor cells and monocytes, thereby inhibiting their reg- ular differentiation into mature DCs (3,23). In addition, our data are in line with very recent reports showing a T cellsuppressive effect of imatinib in vitro and in vivo (4,5,26).…”
Section: Discussionsupporting
confidence: 90%
“…3,4 The missing self-hypothesis 5 does not explain the antileukemic activity of autologous or allogeneic HLA-matched NK cells, as myelogenous leukemia cells always retain HLA class I antigen expression. 6 However, we and others found that HLA-matched or autologous NK cells can induce leukemia cell elimination in vitro and in vivo through ligands of NK-activating receptors on myeloid leukemia cells, suggesting a role of NK cells in graft-versus-leukemia (GVL) activity in HLAidentical sibling SCT. 3,7 The in vivo potential of NK cells in HLA-matched SCT has been recently described by Savani et al 4 In this study of factors associated with early molecular remission in CML after T-celldepleted allogeneic SCT, we made two critical observations: first, the day-30 NK count (NK30) was associated with outcome,…”
mentioning
confidence: 89%
“…3 More recently, it has been reported that exposure to imatinib only minimally affects the differentiation of bcr-abl þ and normal monocytes into DCs and does not impair the DC-mediated polarization of naive CD4 þ T cells. 4 In contrast, Appel et al 5,6 demonstrated that imatinib efficiently inhibits the differentiation of CD34 þ hematopoietic progenitors and monocytes into DCs and their ability to induce cytotoxic T-cell responses. Whereas all these reports are based on DCs that are generated after several days in the presence of various cytokines studies investigating the impact of imatinib on native human blood DCs are very limited.…”
mentioning
confidence: 98%
“…c-Abl is a non-receptor tyrosine kinase protein that regulates cellular proliferation and cytoskeletal remodeling (40). c-Abl is also involved in the differentiation of diverse cell types, including adipocytes, osteoblasts, and dendritic cells (41)(42)(43). The results of our study suggest that c-Abl tyrosine kinase signaling may play an important role in the differentiation of CD14 + monocytes into fibrocytes.…”
Section: Pdgf-bb-inducedmentioning
confidence: 64%